Дальневосточные зарисовки Александра Яковлева - Шапченко, Юлия (Acta Polono-Ruthenica, 2019)
Alexandre Yakovlev was a famous Russian painter, graphic and theatre artist, a graduate from the Imperial Academy of Arts and a member of the “World of Art”. In 1917 by the order of the Academy (material collection to decorate interiors of the Kazanian railway station) Yakovlev went to Beijing, then he traveled a lot throughout China, Mongolia and Japan. He explored Chinese and Japanese theaters, as a result he made many ethnographic sketches, portraits and photographs. He arranged the exhibition of his drawings in Shanghai (in 1919). Finding out about the revolution in Russia he emigrated to France. Since 1919 he lived in Paris. He showed multiple works of Far Eastern cycle at personal exhibitions in Paris (Barbazanges Gallery, 1920 and 1921; together with V. Shuhaev), London (Grafton Gallery, 1920) and Chicago (Art Institute, 1922). In 1922 the pub-lisher Lucien Vogel published an album Drawings and paintings of the Far East, which included 50 reproductions of Yakovlev’s Far-East cycle (the book was designed by Shuhaev). At the same time the artist produced an album on the Chinese theater with accompanying text by a Chinese author Zhu Kim-Kim. In 1931–1932 Yakovlev took part in the “Yellow Cruise” arranged by the “Citroen” company. From this expedition he brought some new series of drawings. At the end of the cruise he presented his artworks in Paris and at foreign exhibitions. This background of the artist’s life is subject to be studied better in Russia.